Edexcel A level Mathematics Pure Mathematics Year 2 Textbook. (2017) - Attwood, Greg; Barraclough, Jack; Bettison, Ian; Goldberg, David; Macpherson, Alistair; Petran, Joe; Pledger, Keith; Smith, Harry; Staley, Geoff; Wilkins, Dave; Moran, Bronwen; Gallick, Keith; et al.
No abstract available